2011
DOI: 10.1097/mnm.0b013e32834207cb
|View full text |Cite
|
Sign up to set email alerts
|

Perfused lung volume to thoracic gas volume ratio (perfused lung fraction) in patients with COPD and in controls

Abstract: The fraction of lung volume receiving blood from the pulmonary artery is reduced in patients with COPD. The degree of underperfusion seems to correlate with the degree of airflow limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They observed that the lung-volume fraction that receives blood from the pulmonary artery was reduced in these patients and that the degree of underperfusion correlated with the FEV 1 :FVC value ( r =0597; P <0.001). 39 …”
Section: Resultsmentioning
confidence: 99%
“…They observed that the lung-volume fraction that receives blood from the pulmonary artery was reduced in these patients and that the degree of underperfusion correlated with the FEV 1 :FVC value ( r =0597; P <0.001). 39 …”
Section: Resultsmentioning
confidence: 99%